Global business today - Hill, Charles W.L. (McGraw-Hill, 2006)
Charles Hill’s Global Business Today, 4e (GBT) has become an established text in the International Business market for its excellent but concise coverage of the key global issues including the cultural context for global business, cross-border trade and investment, the global monetary system and competition in the global environment. GBT’s concise chapters give a general introduction to international business - emphasizing the environmental factors, with less coverage of operations. Charles Hill is renowned for his attention to research trends and that is evident in Global Business Today, 4e through a variety of real world examples and cases from small, medium, and large companies throughout the world